1995
DOI: 10.1126/science.7871433
|View full text |Cite
|
Sign up to set email alerts
|

Choice of STATs and Other Substrates Specified by Modular Tyrosine-Based Motifs in Cytokine Receptors

Abstract: Many members of the cytokine receptor superfamily initiate intracellular signaling by activating members of the Jak family of tyrosine kinases. Activation of the same Jaks by multiple cytokines raises the question of how these cytokines activate distinct intracellular signaling pathways. Selection of particular substrates--the transcriptional activator Stat3 and protein tyrosine phosphatase PTP1D--that characterize responses to the ciliary neurotrophic factor-interleukin-6 cytokine family depended not on which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
710
2
6

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 930 publications
(751 citation statements)
references
References 32 publications
33
710
2
6
Order By: Relevance
“…We and others have previously shown that the addition of`tyrosine modules' from gp130 or from other receptors to the membrane proximal region of gp130 resulted in receptors capable of activating STATs Stahl et al, 1995). We therefore generated clones expressing chimeric receptor constructs with tyrosine modules Y767 or Y814 from gp130 ( Figure 3).…”
Section: Gp130-mediated Growth Inhibition Requires the Presence Of Stmentioning
confidence: 99%
See 3 more Smart Citations
“…We and others have previously shown that the addition of`tyrosine modules' from gp130 or from other receptors to the membrane proximal region of gp130 resulted in receptors capable of activating STATs Stahl et al, 1995). We therefore generated clones expressing chimeric receptor constructs with tyrosine modules Y767 or Y814 from gp130 ( Figure 3).…”
Section: Gp130-mediated Growth Inhibition Requires the Presence Of Stmentioning
confidence: 99%
“…Although gp130-stimulation leads to a transient SHP-2 phosphorylation in A375 cells (Figure 5a), SHP-2 activation cannot be essential for the growth arrest of A375 cells since the chimeras Y767 and Y814 lack tyrosine residue Y759 of gp130 required for SHP-2 activation (Stahl et al, 1995) while still being able to mediate growth arrest ( Figure 4). To investigate the e ect of SHP-2 activation without concomitant STAT activation, transfectants were generated that expressed receptors containing tyrosine module Y759 (Figure 3, lower panel).…”
Section: Shp-2 Activation Without Concomitant Stat Activation Does Nomentioning
confidence: 99%
See 2 more Smart Citations
“…Upon cytokine receptor oligomerization, JAKs phosphorylate the receptor molecules on tyrosine. This allows the receptor to bind STATs through their SH2 domains (Heim et al, 1995;Stahl et al, 1995). STATs are then phosphorylated by JAKs on a conserved tyrosine residue, which drives the subsequent events of STAT release, dimerization and nuclear translocation (Briscoe et al, 1996).…”
Section: Introductionmentioning
confidence: 99%